2012
DOI: 10.1002/jcb.24165
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17 mediates estrogen‐deficient osteoporosis in an Act1‐dependent manner

Abstract: Estrogen-deficient osteoporosis may be an inflammatory disorder and we therefore asked if IL-17 participates in its pathogenesis. Deletion of the principal IL-17 receptor (IL-17RA) protects mice from ovariectomy (OVX)-induced bone loss. Further supporting a central role of IL-17 in its pathogenesis, OVX-induced osteoporosis is prevented by a blocking antibody targeting the cytokine. IL-17 promotes osteoclastogenesis by stimulating RANK ligand (RANKL) expression by osteoblastic cells, mediated by the IL-17RA SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 45 publications
(55 reference statements)
3
86
1
Order By: Relevance
“…In fact, in a recent study we have observed reduced atherosclerotic plaque burden in female Apoe/TRAF3IP2 double knock-out mice fed a Western diet (52). In another study, TRAF3IP2 was shown to mediate estrogen-deficient osteoporosis (53), further supporting the hypothesis that female sex hormones may negatively regulate TRAF3IP2 expression via mechanisms yet to be investigated.…”
Section: Trafip2 In Adverse Cardiac Remodelingmentioning
confidence: 65%
“…In fact, in a recent study we have observed reduced atherosclerotic plaque burden in female Apoe/TRAF3IP2 double knock-out mice fed a Western diet (52). In another study, TRAF3IP2 was shown to mediate estrogen-deficient osteoporosis (53), further supporting the hypothesis that female sex hormones may negatively regulate TRAF3IP2 expression via mechanisms yet to be investigated.…”
Section: Trafip2 In Adverse Cardiac Remodelingmentioning
confidence: 65%
“…Increased IL-17 levels were associated with decrease mineralization of bone. De Selm [17] observed that blocking IL-17 signaling prevents estrogen deficiency mediated osteoporosis by inhibiting osteoclastogenesis in animal model. Molnar et al [18] in his study on human subjects observed strong association of estrogen deficiency with elevated IL-17 level in post menopausal females.…”
Section: Methodsmentioning
confidence: 99%
“…The discrepancy between reports from us and other attesting to a role of T cells (7,32,33,35,37,39,40) and that of Lee at al. (38) is likely explained by differences in the experimental design, the lack of B cells in some models, and compensatory mechanisms such as an increase in natural killer (NK) cells producing the osteoclastogenic factor IL-17 (41).…”
Section: T Cells Mediate the Effects Of Estrogen Deficiency In Bonementioning
confidence: 99%
“…The differentiation of the Th17 subset of CD4þ cells is inhibited by estrogen via a direct effect mediated by ERa (42). The specific contribution of Th17 in ovx induced bone loss remains controversial as one study reported that IL-17R null mice are more susceptible to ovx induced bone loss than controls (43), while another group found mice lacking IL-17R and mice treated with anti IL-17 antibody to be protected against ovx induced bone loss (44). Because IL-17 signaling has been documented to produce bone loss only in the context of severe inflammation, the fact that it is an essential component of ovx induced bone loss is apparently surprising.…”
Section: T Cells Mediate the Effects Of Estrogen Deficiency In Bonementioning
confidence: 99%